The Past: History or Memory - Acuña Rodríguez, Olga Yanet (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article considers the connection between history and memory as foundations for knowledge of the past. Firstly, this article is interested in the differentiation between memory and history. Regardless of the fact that both of these are effective tools for the reconstruction of the past, memory and history have relevant differences which have been studied from multiple viewpoints – not exclusively a historical one –,facilitating a fascinating academic and intellectual debate. Secondly, this article analyzes the way in which these two concepts have been addressed in the irst six issues of Historia Y MEMORIA journal, which proposes historiography, as a ield of analysis that allows researchers in the social sciences to discuss the contributions of memory to historiographical construction, and how memory contributes to the creation of both individual and collective remembrance. In the irst six journal issues, the relationship between history and memory is found in the subject matter, theoretical approaches, use of sources and proposed methodologies, bringing us closer to alternative prognoses about the past, that include a permanent dialogue with the present.